Tajdid Muhammadiyah in Progressive Education: Symbiosis of Reform and Modernization in the 4.0 & 5.0 Era - Setyaningrum, Indah; Istanto, Istanto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This research examines the concept of tajdid in Muhammadiyah's progressive education as a conceptual framework that integrates the reform of Islamic values with the modernization of the education system in response to the challenges of the Industrial Revolution 4.0 and Society 5.0. The method used in this study is qualitative with a literature approach (Library Research), this study analyzes books, scientific journal articles, previous studies, and official documents of Muhammadiyah related to Islamic education, progressive education, reform, and modernization. The findings show that tajdid functions as an ideological foundation and operational strategy in the development of Muhammadiyah education, directing the integration of religious knowledge and general knowledge, progressive pedagogical methods, and adaptive educational governance. Muhammadiyah education emphasizes critical thinking, technological literacy, character building, and social responsibility through a holistic and humanist educational approach rooted in Islamic values. The concept of progressive education reflects an effort to align Islamic teachings with contemporary social realities, by adopting progressive educational thinking while maintaining a strong religious orientation. In the context of rapid technological advancement, Muhammadiyah education positions technology as a means to improve the effectiveness of learning and human welfare, not as the ultimate goal. This research makes a conceptual contribution by strengthening the understanding of tajdid as a framework that shapes the direction of Muhammadiyah education towards a transformative, adaptive, and values-based Islamic education model, which remains relevant in the midst of ongoing social and technological changes.